Charge control of the inverse trans-influence - la Pierre, Henry Storms; Rosenzweig, Michael; Kosog, Boris; Hauser, Christina; Heinemann, Frank Wilhelm; Liddle, Stephen T.; Meyer, Karsten (Chemical Communications, 2015)
The synthesis and characterization of uranium(VI) mono(imido) complexes, by the oxidation of corresponding uranium(V) species, are presented. These experimental results, paired with DFT analyses, allow for the comparison of the electronic structure of uranium(VI) mono(oxo) and mono(imido) ligands within a conserved ligand framework and demonstrate that the magnitude of the ground state stabilization derived from the inverse trans-influence (ITI) is governed by the relative charge localization on the multiply bonded atom or group.